Two Newly Recorded Species of the Lobster Family Scyllaridae (Thenus indicus and Scyllarides haanii) From South of Java, Indonesia - Yusli Wardiatno; Agus Alim Hakim; Ali Mashar; Nurlisa Alias Butet; Luky Adrianto (Bogor Agricultural University, Indonesia, 2016)
Two species of slipper lobster, Thenus indicus Leach, 1815, and Scyllarides haanii De Haan, 1841, are reported for the first time from the coastal waters of South of Java, part of the Indian Ocean. A total of two specimens, one specimen of T. indicus from Palabuhanratu Bay and one specimen of S. haanii from Yogyakarta coastal waters, were collected in April and September 2015, respectively. Descriptions and illustrations of the morphological characteristics of the two species and their habitat are presented.